ANALISIS BUDAYA LO’MOKA DI SAMPULUNGAN KABUPATEN TAKALAR (Karya Ilmiah Mahasiswa (KIMA), 2022)
In society there are several cultures that include them. One of them is the culture that exists in the community in the village of Sampulungan, Takalar Regency. The culture of the Sampulungan community is certainly not one, but the author chooses to focus on one culture only, namely the culture of the Lo'moka title. Lo'moka itself is a title that is carried by certain and elected people in the village of Sampulungan. In this case, not everyone, not even just anyone with the title Lo'moka even though he is from the Sampulungan community. The focus of this research is on historical facts about the Lo'moka title in Sampulungan village, Takalar Regency and whether the Lo'moka title is still used in society today. Analysis of Lo'moka Culture in Sampulungan, Takalar Regency is the title of the research that will be investigated by researchers and guided by Hariratul Jannah and Hj. Emma Bazergan. This study aims to determine the historical facts about the Lo'moka title in Sampulungan village and the current use of the Lo'moka title. This study uses a qualitative descriptive method as a research method. Data were collected from direct interviews in Sampulungan village. The author finds that the title Lo'moka is a title that comes from the king of Gowa which is bestowed on a man who has won a competition held by the king of Gowa.